Brain and eye involvement in McCune-Albright Syndrome: clinical and translational insights - Mascioli, Ilaria; Iapadre, Giulia; Ingrosso, Diletta; Donato, Giulio Di; Giannini, Cosimo; Salpietro, Vincenzo; Chiarelli, Francesco; Farello, Giovanni (Frontiers in Endocrinology, 2023)
McCune-Albright Syndrome (MAS) is a rare mosaic (post-zygotic) genetic disorder presenting with a broad continuum clinical spectrum. MAS arises from somatic, activating mutations in the GNAS gene, which induces a dysregulated Gsα-protein signaling in several tissues and an increased production of intracellular cyclic adenosine monophosphate (cAMP). Overall, MAS is a rare disorder affecting less than 1/100,000 children and, for this reason, data establishing genotype-phenotype correlations remain limited. Affected individuals clinically present with a variable combination of fibrous dysplasia of bone (FD), extra-skeletal manifestations (including cafeí-au-lait spots) and precocious puberty which might also be associated to broad hyperfunctioning endocrinopathies, and also gastrointestinal and cardiological involvement. Central nervous system (CNS) and eye involvement in MAS are among the less frequently described complications and remain largely uncharacterized. These rare complications mainly include neurodevelopmental abnormalities (e.g., delayed motor development, cognitive and language impairment), CNS anomalies (e.g., Chiari malformation type I) and a wide array of ophthalmological abnormalities often associated with vision loss. The pathophysiological mechanisms underlying abnormal neurological development have not been yet fully elucidated. The proposed mechanisms include a deleterious impact of chronically dysregulated Gsα-protein signaling on neurological function, or a secondary (damaging) effect of (antenatal and/or early postnatal) hypercortisolism on early pre- and post-natal CNS development. In this Review, we summarize the main neurological and ophthalmological features eventually associated with the MAS spectrum, also providing a detailed overview of the potential pathophysiological mechanisms underlying these clinical complications.